Evaluation of Damage in Concrete Under Uniaxial Compression by Measuring Electric Response to Mechanical Impact; Journal of Nondestructive Evaluation; Vol. 36, iss. 2 - Fursa T. V. Tatyana Viktorovna; Dann D. D. Denis Dmitrievich; Petrov M. V. Maksim Vyacheslavovich; Лыков А. Е. Александр Евгеньевич (2017, 2017)
Title screen